IMAGE SEGMENTATION- A REVIEW (International Journal of Engineering and Computer Science, 2014)
Image Processing is a procedure to translate an image into digital figure and carry out some operations to get a better image and take out useful information from it. There are many techniques of digital image processing like image enhancement, compression and reconstruction which are discussed in this paper. Image segmentation is an important method of image processing which is widely used in these days. Further image segmentation is divided into different categories in which edge segmentation is very common and effective in the latest research area.